Spatial Analysis of Health Care Facilities for Equitable Access: A Case Study of Abakaliki Local Government Area, Ebonyi State - Idhoko, K. E.; Ekemezie, E. J.; Ozurumba, C. D. (Journal of Spatial Information Sciences, 2026)
This study presents the development of a comprehensive geospatial database and digital mapping of healthcare facilities within Abakaliki Local Government Area, Ebonyi State, utilizing Geographic Information System (GIS) techniques. Primary geospatial data were collected through Global Positioning System (GPS) field surveys, complemented by secondary data obtained from the archival resources of the GIS department within the Office of the Surveyor General of Ebonyi State. Spatial data processing and analysis were conducted using QGIS version 2.4.0. The spatial analysis of health care facilities in Abakaliki Local Government Area revealed significant disparities in their distribution, underscoring challenges in equitable access to healthcare services across the metropolis. A total of 151 health care facilities were identified and categorized into clinics (130), hospitals (8), primary health centers (7), and health laboratories (6). This composition highlights a predominance of clinics with relatively fewer hospitals and other specialized facilities, reflecting the general structure of health service provision in the area. These findings highlight critical gaps in healthcare accessibility, underscoring the need for strategic planning and policy interventions aimed at enhancing the spatial equity of healthcare service delivery within Abakaliki LGA.